KERAGAAN USAHATANI LAHAN KERING PADA PETANI MISKIN DI WILAYAH TIMOR BARAT NUSA TENGGARA TIMUR (DRY LAND PERFORMANCE OF POOR FARMERS IN WEST TIMOR REGION, EAST NUSA TENGGARA) - Johanes G. Sogen; Matheos F. Lalus (Universitas Nusa Cendana, 2014)
A survey was focused on the model of dry land farming performance of poor farmer was conducted at West Timor region for three months. The objectives of the study was: (1) to identify and compare: (a) flow system of goods, money and services in or out of a farming; (b) level of cash and non cash income; (c) the capability of farming in contributing repayment of capital and family labor; and (d) the capability repayment of farm debt and capital ratio of smallholders; (2) to identify and analyze factors influencing on the cash income; (3) to study the combination of group of farm contributing optimum income for poor farmer; and 4) to identify and analyze strength and weaknesses of strategy used by poor farmers in overcome their low income. Multiple stages sampling was established. Two selected districts, four sub-districts and 8 villages were purposively sampled. Whilst 186 poor farmers were randomly selected. Data were analyzed using input-output analyzes, comparative analyzes, linear programming and univariat. Results of analysis showed that total income obtained was Rp.5,961,061.40 which coming from paddy, corn, cassava and sweet potatoes, peanuts, vegetables and livestock. 46,39% of total income was cash income. Livestock was the greatest contributor compared to others (37,90% of total income). From total cash income obtained, the livestock contributing approximately 41,60%, implied that livestock was being the source cash income for poor farmer in rural area. In farming production, the farmer had invested the capital of Rp.9,708,066.61. The operator’s farm income was Rp.1.901.093,41/annual while operator’s farm labor earnings and family farm labor earnings were Rp.9.061.315,07 and Rp.11.956.315,07, respectively. Return on investment (ROI) was 160%. Meant that capital productivity was good enough where the capital had capability to give profit for poor farmer. Thus, farming was a profitable effort. Family income as cumulative of income from on farm, off farm and non farm was Rp.13.253.671.07 annually where only 20.86% out of this was cash income. In addition, the significant factors influencing on the cash income farming was land tenured, number of animal raised and family labor. Result of linear programming indicated that the best combination of farming activities giving optimum income was paddy, corn, cassava and sweet potatoes, peanuts, cattle, pig, goats, and chickens and also non farm activity. In summary, farming is at present to be an economically feasible and profitable enterprise. Through applying the optimum combination of each enterprise the poor farmer will obtain maximum income. ABSTRAK Sebuah survei difokuskan pada model kinerja pertanian lahan kering petani miskin dilakukan di wilayah Timor Barat selama tiga bulan. Tujuan dari penelitian ini adalah: (1) untuk mengidentifikasi dan membandingkan: (a) sistem arus barang, uang dan jasa dalam atau keluar dari pertanian; (b) tingkat kas dan pendapatan non cash; (c) kemampuan pertanian dalam memberikan kontribusi pembayaran kembali modal dan tenaga kerja keluarga; dan (d) pelunasan kemampuan utang pertanian dan rasio modal petani; (2) mengidentifikasi dan menganalisis faktor-faktor yang berpengaruh terhadap pendapatan tunai; (3) mempelajari kombinasi kelompok pertanian memberikan kontribusi pendapatan yang optimal bagi petani miskin; dan 4) mengidentifikasi dan menganalisis kekuatan dan kelemahan strategi yang digunakan oleh petani miskin dalam mengatasi pendapatan mereka rendah. Beberapa tahap pengambilan sampel dilakukan. Dua kabupaten terpilih, empat kecamatan dan 8 desa dilakukan secara purposive sampel. Sementara 186 petani miskin dipilih secara acak. Data dianalisis dengan menggunakan analisis input-output, analisis komparatif, pemrograman linear dan univariat. Hasil analisis menunjukkan bahwa total pendapatan yang diperoleh adalah Rp.5,961,061.40 yang berasal dari padi, jagung, ubi kayu dan ubi jalar, kacang tanah, sayuran dan ternak. 46,39% dari total pendapatan adalah pendapatan tunai. Ternak adalah penyumbang terbesar dibandingkan dengan orang lain (37,90% dari total pendapatan). Dari total pendapatan kas yang diperoleh, ternak memberikan kontribusi sekitar 41,60%, tersirat bahwa ternak menjadi sumber pendapatan tunai bagi petani miskin di daerah pedesaan. Dalam pertanian produksi, petani telah menginvestasikan ibukota Rp.9,708,066.61. Pendapatan usahatani operator adalah Rp.1.901.093,41 / tahunan, sementara pendapatan buruh tani operator dan pendapatan buruh tani keluarga masing-masing adalah Rp.9.061.315,07 dan Rp.11.956.315,07. Pengembalian investasi (ROI) adalah 160%. Berarti bahwa produktivitas modal itu cukup baik di mana modal memiliki kemampuan untuk memberikan keuntungan bagi petani miskin. Dengan demikian, pertanian adalah usaha yang menguntungkan. Pendapatan keluarga sebagai kumulatif pendapatan dari on farm, off farm dan non farm adalah Rp.13.253.671.07 per tahun di mana hanya 20,86% dari ini adalah pendapatan tunai. Selain itu, faktor-faktor yang signifikan berpengaruh terhadap pertanian pendapatan tunai adalah tanah tetap, jumlah hewan dibesarkan dan keluarga tenaga kerja. Hasil pemrograman linear menunjukkan bahwa kombinasi terbaik dari kegiatan pertanian memberikan pendapatan yang optimal adalah padi, jagung, ubi kayu dan ubi jalar, kacang tanah, ternak, babi, kambing, dan ayam serta kegiatan non pertanian. Singkatnya, pertanian pada saat ini menjadi suatu perusahaan layak secara ekonomis dan menguntungkan. Melalui menerapkan kombinasi optimum dari masing-masing perusahaan petani miskin akan memperoleh pendapatan yang maksimal.